Zapisz w jak najprostszej postaci.a) −3(5a+ 4b) − (2a−b)b) 2x(x− 1) − 4(2x2− 1)c) (a−b)(3a+ 2b)d) (x2+ 1)(x− 3) − 2x2(x+ 1)



Odpowiedź :

a)

-3(5a+4b)-(2a-b)= -15a+(-12b)-2a+b=(-17a)+(-11b)

b)

2x(x-1)-4(2x2-1)=2x²-2x-8x×(-8)+4=2x²-2x+64x+4=2x²+62x+4

c)

(a-b)(3a+2b)=3a²+2ab-3ab-2b²=3a²-ab-2b²

d)

(2x+1)(x-3)-2x2(x+1)=2x²-6x+x-3-2x(2x+2)=2x²-6x+x-3-4x²-4x=(-2x²)-5x-3

Odpowiedź:

a) −3(5a+ 4b) − (2a−b)=

- 15a - 12b - 2a+b= - 17a - 11b

b) 2x(x− 1) − 4(2x2− 1)=

2x^2 - 2x - 8x^2+4= - 6x^2 - 2x+4

c) (a−b)(3a+ 2b)=

3a^2+2ab-3ab-2b^2=3a^2 - ab - 2b^2

d) (x2+ 1)(x− 3) − 2x2(x+ 1) =

x^3 - 3x^2+x - 3 - 2x^3 - 2x^2= - x^3 - 5x^2+x - 3  

Szczegółowe wyjaśnienie: